Anomeric Stereoauxiliary Cleavage of the C−N Bond of d‐Glucosamine for the Preparation of Imidazo[1, 5‐a]pyridines. Issue 29 (8th April 2022) - Zeng, Kui; Ye, Jin; Meng, Xintong; Dechert, Sebastian; Simon, Martin; Gong, Shuaiyu; Mata, Ricardo A.; Zhang, Kai
Abstract: The targeted cleavage of the C−N bonds of alkyl primary amines in sustainable compounds of biomass according to a metal‐free pathway and the conjunction of nitrogen in the synthesis of imidazo[1, 5‐a]pyridines are still highly challenging. Despite tremendous progress in the synthesis of imidazo[1, 5‐a]pyridines over the past decade, many of them can still not be efficiently prepared. Herein, we report an anomeric stereoauxiliary approach for the synthesis of a wide range of imidazo[1, 5‐a]pyridines after cleaving the C−N bond of d ‐glucosamine (α‐2° amine) from biobased resources. This new approach expands the scope of readily accessible imidazo[1, 5‐a]pyridines relative to existing state‐of‐the‐art methods. A key strategic advantage of this approach is that the α‐anomer of d ‐glucosamine enables C−N bond cleavage via a seven‐membered ring transition state. By using this novel method, a series of imidazo[1, 5‐a]pyridine derivatives (>80 examples) was synthesized from pyridine ketones (including para ‐dipyridine ketone) and aldehydes (including para ‐dialdehyde). Imidazo[1, 5‐a]pyridine derivatives containing diverse important deuterated C(sp 2 )−H and C(sp 3 )−H bonds were also efficiently achieved. Abstract : An α‐anomeric stereoauxiliary strategy for the targeted cleavage of C−N bonds in d ‐glucosamine was achieved through a seven‐membered ring transition‐state intermediate and the simultaneous incorporation of amine moieties in imidazo[1, 5‐a]pyridines. This method provides a novel strategy for the C−N bond cleavage and unlocks efficient access to diverse imidazo[1, 5‐a]pyridines blocks bearing versatile functional groups.